HAART-associated risk of preeclampsia in HIV+ women - Cassidy-Matthews, Chenoa (Université d'Ottawa | University of Ottawa, 2015)
Background: Until the advent of highly active antiretroviral therapy (HAART) in 1996, HIV infections were considered a death sentence. In 2013, an estimated 1,400,000 million pregnant women were living with HIV globally, all of whom were at risk of mother-to-child-transmission. Thankfully, many women have access to HAART, the gold standard treatment. However, there are concerns about risks of pregnancy complications associated with HAART, such as preeclampsia, characterized by high blood pressure and sometimes proteinuria. Objectives: To conduct a structured literature review to determine whether there is a relationship between HAART and preeclampsia in HIV+ women, and implications for women in southern Africa. Methods: Five major databases were searched using a comprehensive search strategy of appropriate keywords, variations, and MeSH terms. The database search generated 106 publications, reduced to 35 after removing duplicates. Titles and abstracts were screened for relevance, and remaining publications were read in full. Those that met inclusion criteria were critically appraised using appropriate CASP checklists for risk of bias. Sample size, target population, study design, interventions, outcomes, and raw data were extracted. Results: 7 publications were included in final analysis, with mixed results. Some show an increased risk of preeclampsia in women receiving HAART, while others show no significant increased risk. Conclusion: There is little consensus in the literature about the relationship between antiretroviral therapies and preeclampsia. Further research is needed in order to protect HIV+ women from severe outcomes during pregnancy while still preventing mother-to-child transmission, especially for women in developing countries with limited access to essential obstetric care and HIV treatment.